Maintaining Social Interaction in the Covid-19 Pandemic Era - Mahmudi Mahmudi (Javanologi: International Journal of Javanese Studies, 2023)
Coronavirus Desease 2019 (Covid-19) is a disease outbreak that emerged in Wuhan, China in December 2019. The emergence of Coronavirus Desease 2019 (Covid-19) caused a stir in people's lives in most parts of the world. Covid-19 is a virus that spreads quickly and easily. Crowds are one of the media for the spread of this virus, so crowds must be eliminated in order to stop its spread. Stopping the crowd has the potential to destroy the social fabric in society. Thus, good social interaction is susceptible to deterioration due to the presence of this virus. That is what attracts the author in conducting research with the title "Maintaining Social Interaction in the Covid-19 Pandemic Era". There are two problems in this research. First, to what extent are the interests of maintaining social interaction in social life.Second, how to maintain social interactions in the midst of the Covid19 pandemic era. This research is a library research using a qualitative approach in the form of a sociological study. From the research results, two conclusions can be drawn. First, as a social being, everyone cannot get away from other people. Everyone needs and everyone is needed, depending on their abilities and needs. Therefore, maintaining social interaction is an obligation. Second, the community is required to be wise in responding to the existence of Covid-19 and social interaction which are two contradictory things. People are not justified in ignoring health protocols to avoid Covid-19. On the other hand, the public is also not allowed to interpret the implementation of the health protocol according to their own wishes. The public must consult a lot with experts in their respective fields.